BE_VERWALTUNGSGERICHT 100 2015 179 vom 18. November 2010 - BE Verwaltungsgericht (2010)
Ablehnung in einem Spitalhaftungsverfahren (Weiterleitung vom 9. Juni 2015 - RA Nr. 2015-1148) | Ausstand/Ablehnung